Comparing cognitive behavioral therapy and systemic therapy for social anxiety disorder: randomized controlled pilot trial (SOPHO‐CBT/ST) - Hunger-Schoppe, Christina; Hilzinger, Rebecca; Klewinghaus, Laura; Deußer, Laura; Sander, Anja; Mander, Johannes; Bents, Hinrich; Ditzen, Beate; Schweitzer, Jochen (Family process, 2020)
This randomized controlled trial (RCT) aimed to pilot the newly developed manualized and monitored systemic therapy (ST) for social anxiety disorder (SAD), as compared to manualized and monitored cognitive behavioral therapy (CBT).
First published: 27 October 2019
Gesehen am 18.01.2021